2009
DOI: 10.1590/s1517-86922009000600005
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do Uso do Estabilizador Active Ankle System® na Altura do Salto Vertical em Jogadores de Voleibol

Abstract: INTRODUÇÃO E OBJETIVO: Na prática do voleibol, as entorses de tornozelo representam 25 a 50% das lesões agudas. Medidas preventivas, como estabilizadores dinâmicos de tornozelo (EDT), são frequentemente utilizadas, porém, há controvérsias se esse dispositivo pode ou não interferir no desempenho esportivo. O objetivo deste estudo foi analisar o efeito do EDT Active Ankle System® (AAS) na altura do salto vertical em jogadoras de voleibol. MÉTODOS: Selecionou-se uma amostra de conveniência de 14 atletas entre 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
(81 reference statements)
1
4
0
Order By: Relevance
“…The active ankle stabilizer didn't show significant difference between the volunteers jump performance, as also was found in the studies of Anjos and Saldanha [10]; Ambegaonkar et al [11]; Cordova et al [1].…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…The active ankle stabilizer didn't show significant difference between the volunteers jump performance, as also was found in the studies of Anjos and Saldanha [10]; Ambegaonkar et al [11]; Cordova et al [1].…”
Section: Discussionsupporting
confidence: 57%
“…One of them performed by Anjos and Saldanha [10] used a volleyball attack gesture; however he also did not find significant differences regarding the use of stabilizer. Nevertheless, Massa [12] concluded that there is a difference in the vertical jump between volleyball athletes in the adult and juvenile category with and without the ankle stabilizer.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…While Distefano et al 7 did not show any alterations in jump landing task. Regarding the countermovement jump, the studies of Rosenbaum et al 14 and Ozer et al 15 showed a reduction in the height of a jump with the use of an ankle brace; in contradiction, the studies of Abián-Vicén et al 16 and Dos Anjos et al 17 showed no effect at all of the use of ankle brace upon the vertical jump. On the other hand, Sacco et al 12 identified a protective effect of the use of an ankle brace (Aircast) during the jump take-off phase, evidenced by the decreasing of the mediolateral GRF.…”
Section: Introductionmentioning
confidence: 95%